2015
DOI: 10.1063/1.4922980
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology and control of buckling dynamics in multicomponent colloidal droplets

Abstract: Articles you may be interested inMicelle-induced depletion interaction and resultant structure in charged colloidal nanoparticle system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Similarly, through hydrothermal route, [40] successfully synthesized 3D flower-like ZnO architectures assembled with numerous nanosheets with the aid of SDS. It has also been demonstrated that SDS is a highly effective structuredirecting agent for producing box-like structures [41] and is observed elsewhere to cause complete suppression of the buckling phenomenon above an optimal value of 1% by weight [42]. Additionally, Blanch et al [39] found out that attractive depletion in SDS was preferential for carbon nanotubes of larger diameter at higher concentrations of SDS.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, through hydrothermal route, [40] successfully synthesized 3D flower-like ZnO architectures assembled with numerous nanosheets with the aid of SDS. It has also been demonstrated that SDS is a highly effective structuredirecting agent for producing box-like structures [41] and is observed elsewhere to cause complete suppression of the buckling phenomenon above an optimal value of 1% by weight [42]. Additionally, Blanch et al [39] found out that attractive depletion in SDS was preferential for carbon nanotubes of larger diameter at higher concentrations of SDS.…”
Section: Introductionmentioning
confidence: 92%
“…The anionic surfactant, sodium dodecyl sulfate (SDS) is perhaps one of the most widely studied surfactant with unique physical properties [33][34][35][36] that has found many applications in science and technology. The role of SDS in evaporation-driven assembly of nanoparticles have been widely explored [6,29,[37][38][39][40][41][42]. For example, [37] used SDS as a capping agent to synthesise rose-like BiOBr nanostructures with exposed {111} facets via a facile solvothermal route.…”
Section: Introductionmentioning
confidence: 99%
“…Given the experimental complexity associated with studying a mobile air-borne droplet, we have used an acoustic levitator to trap a droplet in the air (tec5) and allowed it to evaporate in a controlled ambience (T∞=28+0.2 °C, RH∞=41+2%). Acoustic levitation 26 has been extensively used to study the evaporation 27 and precipitation dynamics of a solute laden droplet 25,28,29,30 . A droplet of the surrogate fluid having an initial diameter D0=550 μm+10 μm is inserted into one of the stable nodes of the acoustic levitator and imaged every 3 seconds at 30 frames per second (see S1 of Supporting Information) till the end of evaporation.…”
mentioning
confidence: 99%
“…A soft matter droplet consisting of polymer solutions or colloidal dispersions can exhibit different morphologies such as buckling [1][2][3][4], wrinkling [5][6][7][8], or cavitation [9][10][11][12] during the drying process. When all solvents evaporate, the soft matter droplets can turn out to be solid, hollow, wrinkled or buckled particles as the final products [13][14][15][16][17].…”
mentioning
confidence: 99%
“…When all solvents evaporate, the soft matter droplets can turn out to be solid, hollow, wrinkled or buckled particles as the final products [13][14][15][16][17]. This drying process, especially spray drying, has been widely utilised to produce micro-particles of different morphologies in industrial circumstances such as food or pharmaceutical particle production [17][18][19][20][21], amorphous material crystallisation [22][23][24], functional encapsulated particle manufacture [25][26][27], etc., where different shapes are achieved by empirically changing the drying temperature, concentration and constitution of the soft matter solution [3,[28][29][30][31][32][33][34].…”
mentioning
confidence: 99%